Penguasaan kosakata dan kalimat praktis Bahasa Inggris bagi siswa SMK - Syamsiarna Nappu; Ratna Dewi; Hidayah Quraisy (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Vocational school graduates are expected to work or be absorbed into the world of work after completing theireducation at the school level. Therefore, the objective of English learning in vocational schools is that students have the abilityand competence to use English as a tool of communication both orally and written that are needed in the world of work.However, vocational students in particular students of SMKN 6 Makassar do not have adequate English knowledge, vocabularyand skills that they can use in work, especially students in the Hospitality and Tourism majors. This community service aims toassist 50 students in the Hospitality and Tourism Classes of SMKN 6 Makassar to gain knowledge, vocabulary and practicalsentences of English. The method used is 3P namely Presentation, Practice and Production. The assistance activities in learningEnglish were carried out for approximately 3 months from July to September 2019. The output targets were students in theHospitality and Tourism Classes having knowledge, vocabulary and practical sentences of English related to hospitality andtourism.